Correlation of interleukin-6 gene expression and idiopathic female infertility - Madhkhoor, Shaymaa Rabeea; K. Alumeri, Jameel (International Journal of Psychosocial Rehabilitation, 2020)
The present investigation was focused on the identification of the interleukin-6 (IL-6) role in the unexplained female infertility. According to this aim, 100 blood samples were collected from fertile (T1), 50 samples, and infertile (T2), 50 samples, women who attended Al-Nasiriyah Children and Obstetrics Hospital, Al-Nasiriyah, Iraq. Enzyme-linked immunosorbent assay (ELISA) detection was performed to recognize the IL-6 concentrations in the blood samples of those women. A real time-quantitative polymerase chain reaction (RT-qPCR) method was used to identify the gene expression (GE) of the IL-6 gene in the blood of those women. The results of the ELISA showed significant (p˂0.05) higher concentrations of the IL-6 in the blood samples of the T2 women, 352.25pg/ml, than those in the blood samples of the T1 women, 152.35pg/ml. Moreover, the RT-qPCR revealed significant (p˂0.05) higher relative GE of the IL-6 gene in the blood samples of the T2 women, 6.892-fold change (FC), than that in the blood samples of the T1 women, 2.488 FC. The current study indicates that IL-6 may have a major role in the unexplained female infertility.